Improvement of Rabbit pellet formulation developed using pineapple leaves - Khairina Safi Mohd Marzuki (2022)
waste is a by-product of pineapple manufacturing that is typically discarded and pollutes the environment. One of the potential approaches to managed pineapple field wastes is by transforming them into animal feeds. In this research, the improvement of rabbit pellet formulation developed using pineapple leaves was investigated. The nutritional value and physical properties of new rabbit pellet formulation developed by using pineapple leaves was compared with commercial rabbit pellets. Therefore, 40 % of pineapples leaves with additional ingredients such as cracked corn, soybean meal, rice bran, vitamin premix, molasses, limestone and salt was used to fulfil the nutritional requirements of rabbit. As a result, 2 kg of pellet was produced at the end of the process. Pellet physical properties like bulk density and porosity was found to be significantly different (P<0.05), while true density showed there was no significant difference (P>0.05) between pineapple leaves pellet with commercial pellet. Chemical analysis was performed to determine the moisture, protein, fat, fibre, ash and sugar content of both samples. The moisture content and fat statistical analysis showed that there was no significant difference (P>0.05) between pineapple leaves pellet with commercial pellet. However, there was significant difference (P<0.05) in protein, fibre, ash and sugar between pineapple leaves pellet with the commercial pellet. Sample of pineapple leaves pellet obtained the highest amount in fibre and protein content in comparisone to the commercial pellet which gives the lowest values of fibre and protein content. In conclusion, among both samples, 40% pineapple leaves pellet was superior in term of nutrient utilisation that is beneficial for rabbit growth in comparison to the commercial pellet. The findings of the study illustrated that the potential of pineapple leaves was beneficial in producing rabbit feedstuff, and also in helping to alleviate the environmental impact of pineapple processing while helping farmers to earn more money, and creating job opportunities.